Effectiveness of a package of postpartum family planning interventions on the uptake of contraceptive methods until twelve months postpartum in Burkina Faso and the Democratic Republic of Congo: the YAM DAABO study protocol - Nguyen Toan Tran; Mary Eluned Gaffield; Armando Seuc; Sihem Landoulsi; Wambi Maurice E. Yamaego; Asa Cuzin-Kihl; Seni Kouanda; Blandine Thieba; Désiré Mashinda; Rachel Yodi; James Kiarie; Suzanne Reier (BMC, 2018)
Abstract Background Postpartum family planning (PPFP) information and services can prevent maternal and child morbidity and mortality in low-resource countries, where high unmet need for PPFP remains despite opportunities offered by routine postnatal care visits. This study aims to identify a package of PPFP interventions and determine its effectiveness on the uptake of contraceptive methods during the first year postpartum. We hypothesize that implementing a PPFP intervention package that is designed to strengthen existing antenatal and postnatal care services will result in an increase in contraceptive use. Methods This is an operational research project using a complex intervention design with three interacting phases. The pre-formative phase aims to map study sites to establish a sampling frame. The formative phase employs a participatory approach using qualitative methodology to identify barriers and catalysts to PPFP uptake to inform the design of a PPFP intervention package. The intervention phase applies a cluster randomized-controlled trial design based at the primary healthcare level, with the experimental group implementing the PPFP package, and the control group implementing usual care. The primary outcome is modern contraceptive method uptake at twelve months postpartum. Qualitative research is embedded in the intervention phase to understand the operational reasons for success or failure of PPFP services. Discussion Designing, testing, and scaling-up effective, affordable, and sustainable health interventions in low-resource countries is critical to address the high unmet need for PPFP. Due to socio-cultural complexities surrounding contraceptive use, this research assumes that this is more effectively accomplished by engaging key stakeholders, including adolescents, women, men, key community members, service providers, and policy-makers. At the individual level, knowledge, attitudes, and behaviors of women and couples toward PPFP will likely be influenced by a set of low-cost interventions. At the health service delivery level, the implementation of this trial will probably require a shift in behavior and accountability of providers regarding the systematic integration of PPFP into their clinical practice, as well as the optimization of health service organization to ensure the availability of competent staff and contraceptive supplies. Trial registration Retrospectively registered in the Pan African Clinical Trials Registry (PACTR201609001784334, 27 September 2016).